Rancang Bangun Peleburan Alumunium Kapasitas 5 kg Menggunakan Kombinasi Vaporizing dan Air Atomizing Burner Dengan Bahan Bakar Limbah Oli - Supriyadi, Tachli; Yuliaji, Dwi (Universitas Ibn Khaldun Bogor, 2015)
Smelting of aluminum using a combination combustion types of vaporizing burner and atomizing burner with fuel waste oil.Preheat using gasoline with boiling method. The maximum flame melting occurs when the pressure of oil tank at 1.5 bar and air volume mixing 5.2 m3/min.The test results are; aluminum mass of 0.5 kg, the furnace temperature of 625oC, smelting time 12 minutes, the fuel consumption of 1.6 liters.